Perkembangan Digitalisasi Mata Uang Dari Perspektif Hadist Dan Hukum Di Indonesia - M. Aldo Dellano; Tajul Arifin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The development of the world, the more developed the financial world is to help humans manage and conduct financial transactions. The advancement of financial technology today is due to weakness factors in the previous financial world where modern or digital finance is more profitable and follows the times to make it easier for humans to transact. Currently the world is facing digitalization of almost all sectors used by humans and the financial world is inevitable, especially digital currencies that offer advantages such as faster transactions between countries with cheap fees, Decentralised so that it is not driven by any central bank is different from fiat where the strength of the currency depends on the country's policy, and digital currencies that are more transparent so that transactions can be tracked by anyone and are minimal from fraud